Impact of dietary guidelines on lifetime exposure to chemical contaminants: Divergent conclusions for two bioaccumulative substances. (November 2020) - Pruvost-Couvreur, Manon; Le Bizec, Bruno; Margaritis, Irène; Volatier, Jean-Luc; Béchaux, Camille; Rivière, Gilles
Abstract: Food based dietary guidelines (FBDGs) are developed to promote appropriate nutrients intake. However, FBDGs may trigger higher exposure to some food chemical contaminants while recommending the consumption of specific food groups that are more contaminated than others. In some cases, the balance between benefits and risks is difficult to achieve. In the present article, we describe the long-term impact of some FBDGs on the exposure to food contaminants. Two examples of bioaccumulative substances were studied: cadmium and PCBs. To this aim, lifetime dietary exposure trajectories were simulated for two populations: the first representing the general French population, the second generated using virtual individuals following national FBDGs during their entire life. Exposure trajectories were then converted into lifetime cadmium and PCB internal concentrations using physiologically based toxicokinetic models. Finally, trajectories were compared with reference values to assess the health risk related to dietary exposures to cadmium and PCBs, for both simulated populations. This work highlights that FBDGs may have a major impact on PCB dietary exposures and lead to significantly higher PCB plasma concentrations than those observed in the general population. In contrast, cadmium exposure is only slightly impacted when FBDGs are followed. This underscores the relevance of taking into account lifetime exposures when establishing FBDGs. Highlights: In France, studied FBDGs are followed by 3–96% of adults. Following FBDGs triggers higher lifetime PCB internal exposures than those of the general population. Following FBDGs has limited impact on lifetime urinary Cd.